2021
DOI: 10.1088/1402-4896/ac1087
|View full text |Cite
|
Sign up to set email alerts
|

Quantum inverted harmonic potential

Abstract: We consider a non-interacting gas under the inverted harmonic potential and present infinitely degenerate non-stationary orthogonal states. We discuss that it has an infinite entropy at the absolute zero temperature. We show that uncertainty in position of a particle under the inverted harmonic potential can be zero as there exists a solution which asymptotes to a Dirac delta function. We obtain a new free particle wave packet using the eigenstates for the inverted harmonic potential. It has unique self-focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Figure 1 represents the approximation of the Kronig-Penney model, the potential to which the other potentials studied will be approximated, and those that meet the condition of Equation (1). The solutions of the potentials displayed in Figure 1 of the associated time-independent SE are commonly special functions [22,23,26,31], while the zero-like potential has its solution as a linear combination of complex exponentials [3].…”
Section: Theoretical Model Background and Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 represents the approximation of the Kronig-Penney model, the potential to which the other potentials studied will be approximated, and those that meet the condition of Equation (1). The solutions of the potentials displayed in Figure 1 of the associated time-independent SE are commonly special functions [22,23,26,31], while the zero-like potential has its solution as a linear combination of complex exponentials [3].…”
Section: Theoretical Model Background and Simulation Detailsmentioning
confidence: 99%
“…Figure 4 shows the energy dispersion and transcendental energy distribution for the linear-like potential with negative intensity calculated using Equations ( 18)- (22).…”
Section: Linear Potential With a Negative Slopementioning
confidence: 99%
See 1 more Smart Citation
“…The inverted oscillator was recently discussed in [14,15] in relation to cosmological problems. Some of the inverted oscillator problems were also considered in [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in Hermitian systems, self-acceleration happens exclusively for non-integrable waves. It was recently demonstrated that it happens even for integrable waves in non-Hermitian systems [2], and the new wave packets were produced using the inverted harmonic potential eigenstates in [3]. These novel wave packets contain boundless energy and a distinct self-focusing property.…”
mentioning
confidence: 99%